Validação da enzima 5-enolpiruvilchiquimato-3-fosfato sintase (EPSP sintase) de Mycobacterium smegmatis como alvo molecular para desenvolvimento de novas moléculas antimicobacterianas - Villegas, Mario Alejandro Duque (2020)
The epidemiological importance of bacteria from the genus Mycobacterium is indisputable and the necessity to find new molecules that can inhibit their growth is urgent. The shikimate pathway, required for the synthesis of important metabolites in bacteria, represents a target for inhibitors of Mycobacterium tuberculosis growth. The aroA-encoded 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS) enzyme catalyzes the sixth step of the shikimate pathway. In this study, we combined gene knockout, gene knockdown and kinetic assays to evaluate aroA gene essentiality and the vulnerability of its protein product, EPSPS synthase from Mycobacterium smegmatis (MsEPSPS), under different nutritional conditions. We demonstrate by an allelic exchange-based gene knockout approach the essentiality of MsEPSPS under rich and poor nutritional conditions. By performing gene complementation experiments with wild-type (WT) and point mutant versions of aroA gene, together with kinetic assays using WT and mutant recombinant proteins, we show that aroA gene essentiality depends on MsEPSPS activity. To evaluate MsEPSPS vulnerability, we performed gene knockdown experiments using the Clustered Regularly Interspaced Short Palindromic Repeats interference (CRISPRi) system. The experiments were performed in both rich and defined (poor) media, using three different repression forces for aroA gene. We only observed growth impairment when bacteria were grown in defined medium without supplementation of aromatic amino acids, thereby indicating that MsEPSPS vulnerability depends on the environment conditions.